Comparison of kinetic theory evaporation models for liquid thin-films. (July 2019) - Aursand, Eskil; Ytrehus, Tor
Highlights: Kinetic-theory evaporation models may describe non-equilibrium evaporation. Liquid films on the micrometer scale require non-equilibrium models. The Moment Method is able to predict the interface temperature jump. Linearized evaporation models are sufficient in thin film evaporation. Abstract: We summarize the background and derivation of non-equilibrium evaporation models from kinetic theory, and demonstrate how they may be applied in the context of fluid mechanics and heat transfer problems. We find that the linearized Boltzmann-equation Moment Method is a good trade-off between complexity and accuracy for practical purposes, and that the use of non-equilibrium evaporation models in general has significant quantitative and qualitative impact on the results.